Prevalence and Characteristics of Isolated Nighttime Masked Uncontrolled Hypertension in Treated Patients - Kang Hee Kim; Jaehoon Chung; Suyoung Jang; Byong-Kyu Kim; Masanori Munakata; Moo-Yong Rhee (Medicina)
Background and Objectives: We evaluated the prevalence and characteristics of isolated nighttime masked uncontrolled hypertension (IN-MUCH) in treated patients. Materials and Methods: Participants aged 20 years or older who were on antihypertensive medication underwent three-day office blood pressure (BP) and 24 h ambulatory BP measurements. Hypertension phenotypes were classified as controlled hypertension (CH), isolated daytime masked uncontrolled hypertension (ID-MUCH), IN-MUCH, and daytime and nighttime masked uncontrolled hypertension (DN-MUCH). Results: Among 701 participants, 544 had valid BP data and controlled office BP (<140/90 mmHg). The prevalence of IN-MUCH was 34.9%, with a higher prevalence of men and drinkers than in those with CH. Patients with IN-MUCH had higher office systolic BP (SBP) and diastolic BP (DBP) than those with CH. The prevalence of IN-MUCH was 37.6%, 38.5%, and 27.9% in patients with optimal, normal, and high-normal office BP levels, respectively. Among IN-MUCH patients, 51.6% exhibited isolated uncontrolled DBP and 41.1% uncontrolled SBP and DBP. Younger age (p = 0.043), male sex (p = 0.033), and alcohol consumption (p = 0.011) were more prevalent in patients with isolated uncontrolled DBP than in those with uncontrolled SBP and DBP. Age and alcohol consumption were positively associated, whereas high-normal office BP exhibited a negative association with IN-MUCH. Conclusions: The IN-MUCH was significantly more prevalent in patients with normal or optimal office BP, posing treatment challenges. Further investigation is needed to determine whether differentiation between isolated uncontrolled DBP and combined uncontrolled SBP and DBP is necessary for prognostic assessment of IN-MUCH.